(untitled) (diségno, 2026)
Shell structures, also known as laminar structures, profoundly influenced the design and construction mentality of the leading ex- ponents of Constructive Rationalism in the first half of the 20th century. The structural art of designers like Eduardo Torroja, Pier Luigi Nervi and Félix Candela achieved its maximum aesthetic expression in this fascinating type of construction, which based static resistance on the shape of the structure itself. This construction archetype –mainly influenced by the geometry and relationship of the structural elements– requires an accurate representation –both in the two-dimensional and three-dimensional spheres– of the spatial elements that compose the work. This is accom-panied by the practical aspect of construction, characterised by the use of concrete with the support of articulated ribs and formwork. This article addresses the main aspects of laminar structures, to which Torroja contributed through the creation of some of his most famous works. The most audacious –both from an architectural and geometric-structural point of view– was undoubtedly the Frontón Recoletos and its roof, whose geometric and constructional peculiarities made the building famous worldwide. Much of the credit for the construction of the shell and its skylights is attributed to the engineer himself, who was responsible for the design, structural calculations and actual construction.